Production of Poly Aluminum Chloride (PAC) from Local Material (Kaolin) - Abbas, Mohaid; Awad, Khalid; Dirar, Alfatih; Abdalla, Momin E.; Elkareem, Abdelshakour A. (University of Khartoum Engineering Journal, 2021)
Poly aluminum chloride (PAC) has many applications such as water treatment, separation of slurry in industrial processes. The basic raw material for PAC production is aluminum oxide ore such as Kaolin, Bauxite, Mica and Silliminite. In this study Kaolin was used and investigated carefully. Kaolin is abundant in the Sudan. The chemical composition is ,CaO, MgO, , L.O.I. For the production of liquid PAC, Kaolin was activated by calcination process to produce intermediate product (alumina,). Then the alumina extracted from calcined Kaolin was leached with hydrochloric acid to produce aluminum chloride. Finally base is added to aluminum chloride to produce PAC. The effects of the various parameters of production process (calcination temperature, acid concentration, residence time, ratio Kaolin-acid W/W) were investigated and the optimum conditions were found. The results showed that the optimum calcination temperature for the samples used, is 1000˚C with 3 hour residence time with alumina extract of 28.76 ppm .The optimum leaching conditions were determined and found at: Kaolin grain size, 200 meshes, Temperature, 90 ˚C, Residence Time 30 min, Acid concentration of 8N (HCL), which yielded 59.89 ppm of alum extract.